URBAN AGRICULTURE AND INCOME CONTRIBUTION: EVIDENCE ACROSS HOUSEHOLD INCOME GROUPS IN YOGYAKARTA - Grahani, Hedwig Ajeng; Ajar, Seno Budhi (Universitas Gunadarma, 2025)
This study investigates how urban farming contributes to household income and the factors shaping income disparities among urban farmers in Yogyakarta, Indonesia. Despite Yogyakarta’s status as a cultural and educational hub, urban poverty and unemployment persist, prompting the exploration of urban farming as an alternative livelihood strategy to enhance household resilience. Using data from 217 urban farming households, the research employs descriptive statistics and income contribution analysis to measure urban farming’s relative role within household earnings, complemented by multiple linear regression to assess the influence of income group and other income sources. The findings reveal substantial variation, with net income ranging from IDR 1.7 million to IDR 123 million after deducting input costs. Urban farming’s contribution to total income was lowest among low–middle income households (1.38%) and highest among middle–high income households (50.06%), with an overall average of 30.98%, indicating a moderate aggregate role. Regression analysis confirms that higher-income households gain more from urban farming, whereas other income sources reduce its relative importance. These results suggest that while urban farming serves as a key income generator for wealthier households, it remains supplementary for poorer ones, underscoring its broader value in strengthening urban food security and supporting targeted policy initiatives to improve productivity and cost efficiency across socioeconomic groups